Characterising the nature of primary care patient safety incident reports in the England and Wales National Reporting and Learning System: a mixed-methods agenda-setting study for general practice - Carson-Stevens, Andrew; Hibbert, Peter; Williams, Huw; Prosser Evans, Huw; Cooper, Alison; Rees, Philippa; Deakin, Anita; Shiels, Emma; Gibson, Russell; Butlin, Amy; Carter, Ben; Luff, Donna; et al. (NIHR Journals Library, 2016)
Background